A randomized-controlled trial with a Canadian electronic pill dispenser used to measure and improve medication adherence in patients with schizophrenia - Emmanuel eStip; Emmanuel eStip; Emmanuel eStip; Philippe D. Vincent; Philippe D. Vincent; Philippe D. Vincent; Catherine eGuevremont; Simon eZhornitsky; Constantin eTranulis; Constantin eTranulis; Constantin eTranulis; Juliette eSablier; et al. (Frontiers Media S.A., 2013)
Objective: Medication adherence is extremely important in preventing relapse and lowering symptoms in schizophrenic patients. However, estimates show that nearly half of these patients have poor adherence. The Brief Adherence Rating Scale (BARS) seems to be the most reliable tool assessing adherence in schizophrenia and shows that the antipsychotic adherence ratio (AAR) is about 49.5 % in schizophrenia. The aim of the study was to test if an electronic pill dispenser named DoPill® improved AAR of schizophrenic patients. Furthermore, we compared AAR obtained by the DoPill® and the BARS, in order to verify whether the DoPill® provides reliable assessment of medication adherence. Methods: The DoPill® is a smart pill dispenser that beeps and flashes at the appropriate time of the day. Each of its 28 compartments is covered by a plastic lamina that, when taken off, sends a signal to the pharmacist. Patients were randomized to the DoPill® or Treatment As Usual group (TAU) for six weeks. The BARS was used as a reference measure. Results: Forty-six percent of patients were deemed to be non-adherent with antipsychotic medication. The mean AAR was 67 % after six weeks. DoPill® recorded better AAR than some of those found in the literature and were lower than the BARS estimate we found. Conclusion: These results suggest that DoPill® is a valid tool that provides more reliable and objective data for the clinician about their patient's adherence, than existing assessment tools like the BARS. Furthermore, the device may help patients successfully manage their medication regimen.